Implementing a GPU-based numerical algorithm for modelling dynamics of a high-speed train. Issue 4 (3rd April 2018) - Sytov, E. S.; Bratus, A. S.; Yurchenko, D.
ABSTRACT: This paper discusses the initiative of implementing a GPU-based numerical algorithm for studying various phenomena associated with dynamics of a high-speed railway transport. The proposed numerical algorithm for calculating a critical speed of the bogie is based on the first Lyapunov number. Numerical algorithm is validated by analytical results, derived for a simple model. A dynamic model of a carriage connected to a new dual-wheelset flexible bogie is studied for linear and dry friction damping. Numerical results obtained by CPU, MPU and GPU approaches are compared and appropriateness of these methods is discussed.